Second cancer after additive chemotherapy in patients with colon cancer: original study - Teufel, Andreas; Li, Moying; Gerken, Michael; Ebert, Matthias; Schlitt, Hans J; Evert, Matthias; Herr, Wolfgang; Klinkhammer-Schalke, Monika (Clinical colorectal cancer and other gastrointestinal malignancies, 2022)
Background - Additive chemotherapeutic treatment of UICC-stage -III / IV colon cancer with fluorouracil, leucovorin and oxaliplatin is widely accepted as current standard of treatment after R0-resection. However, as patients.. survival is increasing, long-term side effects of chemotherapeutic agents such as second cancer development are becoming increasingly important. - Patients - We therefore investigated a total of 2 856 Patients with UICC-stage III / IV colon cancer, 223 of whom (7.8%) had developed a subsequent second cancer. - Results - Median follow-up was 73.2 months (range 209.9 months, 95%-CI 69.8-76.9). Most frequent second cancers were prostate cancer (18.4%), colon cancer (16.1%), breast cancers (8.1%), lung cancer (8.1%), rectal cancer (4.9%) and uterine cancer (4.9%). However, in comparison to non-treated patients this did not represent a significantly increased risk for subsequent second cancer in patients after treatment with additive chemotherapy. Of interest, our data suggest a significantly decreased second cancer rate in patients treated with FOLFOX compared to FUFOL for additive treatment. - Conclusions - Second cancer development was not increased after additive chemotherapy for colon cancer, which is a novel aspect in the ongoing discussions on reduction of adjuvant treatment to 3 months or treatment of lymph node negative patients. Novelty and Impact Statement To our knowledge, this is the first population-based study analyzing second cancer development after additive chemotherapy in patients with UICC III-IV colon cancer. The results have an important impact on the surveillance and long-term follow-up of cancer patients.